Professional Development and Teachers’ Digital Art Toward Enhanced Instructional Skills - Lin, Xinyao (International Journal of Social Sciences and Public Administration, 2024)
Incorporating digital art into educational curricula confronts art teachers with both prospects and difficulties, necessitating a constant improvement of their teaching abilities to address the changing requirements of students in the digital era. This research assessed the professional development and digital art teaching skills of art instructors to identify areas that need improvement and to guide the construction of an expanded instructional program. The results indicate that art instructors typically consider professional development opportunities to be helpful. However, their proficiency in digital art education is assessed as average in many areas, such as technical expertise, digital art approaches, and media literacy. Furthermore, a notable and favorable association was discovered between the professional growth of art instructors and their proficiency in instructing digital art. This underscores the need of continuous training and improving their abilities. These results suggest the need for an Enhanced Digital Art Instructional Skills Program, which aims to provide art instructors with the necessary skills to conduct effective and ethically acceptable digital art education. This curriculum prioritizes the development of technical skills, expertise in teaching methods, ethical awareness, and cooperation among educators to promote the growth of creativity, critical thinking, and digital literacy in students. Assessment and feedback procedures will be put in place to evaluate the program’s efficacy and guarantee ongoing enhancement.